Long-term incidence of first hospital-recorded atrial arrhythmias and all-cause mortality after percutaneous patent foramen ovale closure: a single-centre cohort linked to Czech nationwide administrative health data - Martina Podolec; Anna Řeháková; Jiří Jarkovský; Aneta Dvořáková; Petr Volf; Petr Neužil; Martin Mates (Frontiers in Cardiovascular Medicine, 2026)
Background Percutaneous patent foramen ovale (PFO) closure is an established strategy for secondary prevention of embolic stroke of undetermined source (ESUS), but long-term arrhythmic and survival outcomes outside randomised trial populations remain incompletely characterised. Using nationwide Czech administrative health registries, we evaluated hospital-recorded atrial arrhythmias (AA), catheter ablation, antithrombotic therapy and mortality over 15 years. Methods Consecutive patients undergoing percutaneous PFO closure at a single Czech tertiary referral centre between 1 January 2010 and 31 December 2024 were linked to nationwide Czech hospitalisation, pharmacy-dispensing and mortality databases. Time-to-event analyses used Kaplan–Meier and Fine–Gray competing-risks estimators; relative survival was estimated using the Pohar–Perme method against age-, sex- and calendar year-matched Czech population life tables. Results A total of 715 procedures were performed in 707 patients [median age 49.4 years (IQR 41.7–59.0); 48.0% male]. Over a maximum follow-up of 14.9 years, 13 patients had a first clinically recognised, hospital-recorded AA (10-year cumulative incidence 2.9%, 95% CI 1.2%–4.6%). Five of the 13 events (38.5%) occurred within the first year, whereas 6 (46.2%) occurred beyond three years; affected patients were predominantly male with a high baseline cardiovascular risk burden. Post-procedural antithrombotic therapy was predominantly antiplatelet-based. The 10-year cumulative incidence of catheter ablation was 2.0% (95% CI 0.6%–3.3%). Thirty-four patients died (10-year all-cause mortality 7.5%, 95% CI 4.8–10.3%), mostly from neoplastic (35.3%) or cardiovascular (32.4%) causes. Relative survival remained close to unity and at no time point fell significantly below it (10-year 1.023, 95% CI 0.982–1.065), indicating no observed excess mortality relative to population life-table expectations. Conclusions Clinically recognised, hospital-recorded AA events after PFO closure were uncommon. Because only 13 events were observed, their timing and association with cardiovascular risk factors are descriptive and hypothesis-generating, and the estimate does not capture total subclinical arrhythmic burden. No observed excess mortality was identified relative to population life-table expectations. These findings support prospective evaluation of risk-stratified rhythm surveillance.